Malaria prevalence and patients’ knowledge, attitude, and preventive practices toward the disease in the Jawi District, Awi Zone, Northwest Ethiopia - Damen, Mekete; Bekele, Damtew; Gashaw, Fikru (Frontiers in Parasitology, 2025)
BackgroundMalaria is the most important parasitic illness causing morbidity and mortality with high prevalence in tropical regions.ObjectiveThis study was aimed at evaluating the 7-year malaria trend and community awareness at Jawi Health Center and primary Hospital in Northwest Ethiopia.MethodsA retrospective and cross-sectional or prospective design were used for the study. The data was analyzed using SPSS version 22 software. The findings were considered significant at P < 0.05.ResultsAmong 62,624 blood films between 2015 and 2021 at Jawi Health Center, 40.9% were positive. Plasmodium falciparum accounted for 85.8%. Women had more mixed infections (P. falciparum and P. vivax) (X2 = 8.9, df = 2, P = 0.011) than men. A greater proportion (20.6%) of malaria cases was observed within the under 5 years age group and the number of malaria cases was higher in September, October, and June. The overall prevalence of malaria was found to be 25.2% and June had the highest proportion (75.6%). In total, 335 (80.9%) respondents recognized mosquito bites as the cause and fever (50%) as a clinical symptom of malaria. More than half of the respondents (60.1%) never sleep under mosquito nets.ConclusionThus, these findings have substantial implications for the trend of malaria prevalence and patient awareness of the disease which support the existing malaria control efforts.